2023
DOI: 10.1007/s00420-023-01962-z
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal perspective on the interplay of job demands and destructive leadership on employees’ work ability in Germany

Abstract: Purpose Work ability as a predictor of early retirement or lengthy/frequent sick leaves becomes more and more relevant due to the demographic change. Therefore, factors, which affect employees’ work ability, need to be further examined with a theoretical base. According to Karasek’s job demands–control (JDC) model, high job demands and low control are related to poor employee health. The subsequent job demands–control support (JDCS) model proposed that a lack of support, also from leaders, has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In our sample, the physical, social, emotional, and organizational job demands were associated with both physical and psychological costs that teachers incurred in fulfilling them. Job demands are one of the crucial determinants that affect WA (Kunz and Millhoff 2023). In the scope of the present study, job demands have been shown to affect PWA rather indirectly.…”
Section: Discussionmentioning
confidence: 61%
“…In our sample, the physical, social, emotional, and organizational job demands were associated with both physical and psychological costs that teachers incurred in fulfilling them. Job demands are one of the crucial determinants that affect WA (Kunz and Millhoff 2023). In the scope of the present study, job demands have been shown to affect PWA rather indirectly.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, in the conceptual model of Sorensen et al ( 9 ), the conditions of work and worker proximal outcomes directly influence other worker outcomes. Lower perceived work ability was, e.g., associated with higher long-term sickness absence and a higher risk of early retirement ( 16 , 17 ). These negative individual worker outcomes produce higher healthcare costs and can affect the organization in the long term ( 10 ).…”
Section: Introductionmentioning
confidence: 99%